1999
DOI: 10.1161/01.cir.100.10.1109
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Collagen Accumulation

Abstract: These results demonstrate that the severity of restenosis after angioplasty correlated with both defective endothelium-dependent relaxation and increased collagen density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(45 citation statements)
references
References 40 publications
(35 reference statements)
5
38
1
Order By: Relevance
“…2,3 Diminished production of vasculoprotective mediators such as NO is a major contributory factor in this pathological process. We hypothesized that adenoviral-mediated gene transfer of NOS genes to the injured carotid artery would increase NO bioavailability within the vessel wall which in turn would enhance endothelial regeneration and inhibit intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Diminished production of vasculoprotective mediators such as NO is a major contributory factor in this pathological process. We hypothesized that adenoviral-mediated gene transfer of NOS genes to the injured carotid artery would increase NO bioavailability within the vessel wall which in turn would enhance endothelial regeneration and inhibit intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…2 Disruption of the endothelial layer following angioplasty procedures has also been implicated in the pathological repair of injured blood vessels. 3 Impaired endothelial function leads to reduced production of key vascular mediators such as nitric oxide (NO) resulting in increased smooth muscle cell proliferation and migration, platelet adhesion and impaired endotheliumdependant vasorelaxation (EDVR). 4 All of the above processes are significant elements in the pathological repair of the injured artery following angioplasty procedures ultimately resulting in intimal hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that collagen accumulation and endothelial dysfunction are associated with constrictive remodeling. 34 Because endothelial vasodilator function is fairly preserved in our porcine model, 35 inflammatory vascular changes associated with collagen accumulation (especially at the adventitia) may play a primary role in the vascular remodeling.…”
Section: Rho-kinase As a Novel Therapeutic Target In Treatment Of Artmentioning
confidence: 97%
“…Collagen matrix 2 and cytoskeletal restructuring 1,6,7 are cornerstones of vascular remodeling. We investigated pecPDI effects in arterial collagen under polarized light.…”
Section: Disrupted Matrix/cytoskeletal Architecture Accounts For Pdiamentioning
confidence: 99%
“…V ascular remodeling involves changes for the whole-vessel circumference and crucially determines lumen caliber 1 in physio(patho)logical situations, such as shear-stress responses, restenosis postangioplasty, [1][2][3] or native atherosclerosis. 1,4 Moreover, cellular mechanisms governing conductance vessel remodeling are likely shared by small-vessel remodeling, for example, in hypertension.…”
mentioning
confidence: 99%